Variação da primeira pessoa do plural no português maranhense - LIMA, Elimária Oliveira (2020)
The present work aims to describe and analyze the variation of the pronouns nós/a gente and the application of verbal agreement with the pronoun nós in Maranhão speech, as well as to establish a comparison between the linguistic behavior of the speakers of the city of Barra do Corda, interior of Maranhão, and São Luís, capital of the State. We have as theoretical and methodological basis the assumptions of the Variationist Theory proposed by Labov (2008 [1972]) and scholars of the personal pronoun in Brazilian Portuguese (PB), such as Omena (1996), Scherre (2005), among others. For the constitution of the corpus, we used the database of the Linguistic Atlas of Maranhão, a project that is in line with the Lusophony Studies and Research Group and with the project “Analysis and Mapping of Morphosyntactic Phenomena in Portuguese Spoken in Maranhão”. The stratification of the corpus takes into account: 12 informants distributed by sex, male and female, two age groups, 18 to 30 years and 50 to 65 years, two locations, São Luís and Barra do Corda and two levels of education, up to the 6th primary education and complete higher education, the latter being analyzed only in the capital. We also analyzed the linguistic variables, subject filling, type of reference, linguistic parallelism, phonic salience and time and verbal mode. The analysis of the pronominal alternation, carried out through the results generated by the program GoldvarbX (SANKOFF, 1988; SANKOFF, TAGLIAMONTE; SMITH, 2005), allowed to verify that people are the preferred way to represent the first person of the plural in the speech of Maranhão, with percentage 71%, although still in co-occurrence with the node that presented a percentage of 29%. In relation to verbal agreement with the pronoun nós, the results generated by the program showed that among Maranhão people there is a greater use of the pronoun with concordance, 64.9%, to the detriment of the use of the pronoun without agreement, 35.1%.